2023
DOI: 10.1111/imcb.12641
|View full text |Cite
|
Sign up to set email alerts
|

The cytosolic DNA sensor AIM2 promotes Helicobacter‐induced gastric pathology via the inflammasome

Abstract: Helicobacter pylori (H. pylori) infection can trigger chronic gastric inflammation perpetuated by overactivation of the innate immune system, leading to a cascade of precancerous lesions culminating in gastric cancer. However, key regulators of innate immunity that promote H. pylori-induced gastric pathology remain ill-defined. The innate immune cytosolic DNA sensor absent in melanoma 2 (AIM2) contributes to the pathogenesis of numerous autoimmune and chronic inflammatory diseases, as well as cancers including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 52 publications
(139 reference statements)
0
1
0
Order By: Relevance
“…As a novel member of the interferon-induced PYHIN proteins, AIM2 plays a significant role in regulating innate immunity [ 23 ]. Recently, numerous studies, including ours, have shown that AIM2 is associated with pathogenic infections [ 24 , 25 , 26 ]. However, the role of AIM2 in pathogenic C .…”
Section: Discussionmentioning
confidence: 99%
“…As a novel member of the interferon-induced PYHIN proteins, AIM2 plays a significant role in regulating innate immunity [ 23 ]. Recently, numerous studies, including ours, have shown that AIM2 is associated with pathogenic infections [ 24 , 25 , 26 ]. However, the role of AIM2 in pathogenic C .…”
Section: Discussionmentioning
confidence: 99%